Performances of the nitric oxide and supplementation of l-arginine on hemodynamic responses and metabolism of body given the practice of physical exercise - Ferreira, Susana América (2012)
Objective: To review on the possible actions of nitric oxide on hemodynamic and metabolic responses of the body before the practice of physical exercise, as well as the effects of L-arginine supplementation on these parameters. Literature Review: The nitric oxide produced by endothelial cells have potent vasodilator action, has an important role in the control of platelet aggregation, preventing the processes of thrombosis and atero-thrombotic diseases, in addition, it balances the relationship ventilation-perfusion in circulation lung, it is also taken as a flag in the regulation of intracellular oxidative metabolism, besides being a regulator of angiogenesis in skeletal muscle. In addition to the likelihood of increased aerobic capacity in submaximal exercise, supplementation with L-arginine has been tested in exercises in character with anaerobic order to reduce accumulations metabolites that reduce and / or to induce fatigue during exercise. However, the greatest benefits of supplementation with L-arginine has been reported in conditions of hypercholesterolemia and coronary diseases. Conclusion: Although there are certain difficulties to possible conclusions due to the different experimental protocols used, the various oral doses of L-arginine given and the lack of greater stiffness in the control of variables allegedly involved in searches.